2021
DOI: 10.20452/pamw.16099
|View full text |Cite
|
Sign up to set email alerts
|

Association between the geographic region and the risk of familial atrioventricular nodal reentry tachycardia in the Polish population

Abstract: Atrioventricular nodal reentry tachycardia (AVNRT) is one of the most common types of regular supraventricular tachycardia (SVT) in patients referred for catheter ablation (CA). This is the first study to determine the frequency of familial form of atrioventricular nodal reentry tachycardia (FAVNRT) in Poland. In this study we revealed relationship between the geographical region of families origin, with diagnosed FAVNRT. The closer distance the family is to Subcarpathia Province, the highest the risk of FAVNR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 11 publications
(25 reference statements)
0
4
0
Order By: Relevance
“…A previous study conducted in Poland reported a familial relationship in 2.91%-4.02% of patients with AVNRT. 1 In another study conducted in 2022, the pathological gene was tried to be identified in sporadic and familial AVNRT cases. This article reports that three possible pathological genes (TRDN, CASQ2 and WNK1) may be responsible for domestic AVNRT cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A previous study conducted in Poland reported a familial relationship in 2.91%-4.02% of patients with AVNRT. 1 In another study conducted in 2022, the pathological gene was tried to be identified in sporadic and familial AVNRT cases. This article reports that three possible pathological genes (TRDN, CASQ2 and WNK1) may be responsible for domestic AVNRT cases.…”
Section: Discussionmentioning
confidence: 99%
“…Atrioventricular nodal reentrant tachycardia (AVNRT) is a common arrhythmia and accounts for approximately 45-65% of paroxysmal supraventricular tachycardias. 1 The average adult heart rate is 60-100 beats/min. However, in AVNRT, this rate is usually higher than 150/min.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Novel techniques are introduced in cardiac electrophysiology [27]. The use of non-fluoroscopic imaging during catheter ablation is more frequently used than before [28,29]. It may be speculated that CFS catheters might be of special value in this setting in patients with congenital heart disease, while in the case of ventricular arrhythmias originating from left ventricle, there may be limited additional benefit in patients with left ventricular hypertrophy.…”
Section: Discussionmentioning
confidence: 99%